Central and Peripheral Mechanism of Acupuncture Analgesia on Visceral Pain: A Systematic Review. (2nd May 2019) - Lee, In-Seon; Cheon, Soyeon; Park, Ji-Yeun
Abstract : Background/Aims . Despite the wide use of acupuncture for the management of visceral pain and the growing interest in the pathophysiology of visceral pain, there is no conclusive elucidation of the mechanisms behind the effects of acupuncture on visceral pain. This systematic review aims to provide an integrative understanding of the treatment mechanism of acupuncture for visceral pain. Methods . Electronic and hand searches were conducted to identify studies that involved visceral pain and acupuncture. Results. We retrieved 192 articles, out of which 46 studies were included in our review. The results of our review demonstrated that visceral pain behaviors were significantly alleviated in response to acupuncture treatment in groups treated with this intervention compared to in sham acupuncture or no-treatment groups. Changes in the concentrations of β -endorphin, epinephrine, cortisol, and prostaglandin E2 in plasma, the levels of c-Fos, substance P, corticotropin-releasing hormone, P2X3, acetylcholinesterase (AchE), N-methyl-D-aspartate (NMDA) receptors, and serotonin in the gut/spinal cord, and the neuronal activity of the thalamus were associated with acupuncture treatment in visceral pain. Conclusions. Acupuncture reduced visceral pain behavior and induced significant changes in neuronal activity as well as in the levels of pain/inflammation-related cytokines and neurotransmitters in the brain-gut axis. Further researches on the thalamus and on a standard animal model are warranted to improve our knowledge on the mechanism of acupuncture that facilitates visceral pain modulation.